Rational emotive behavior therapy to overcome anxiety post-flood disaster - Akhmad Sugianto; Ririanti Rachmayanie J.; Selamad Riyadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
The purpose of this study was to test the validity and practicality of the REBT guidebook and to analyze the effectiveness of group counseling using the REBT approach. The type of research used is experimental with a pretest-posttest control group design. The instrument used in this research is the anxiety scale adopted from Max Hamilton, namely the Hamilton Anxiety Rating Scale (HAM-A) and interviews. The sample in this study amounted to 10 people who were divided into 2 groups, namely 5 control groups and 5 treatment groups. The data analysis technique used to test the effectiveness used the Man Whitney test formula, while the validity and practicality test of the manual used the ideal criterion formula. The results showed that the REBT guidebook was valid and practical to use in the field based on an assessment by 2 expert test persons. Based on the Man Whiteney test, the result (0.046 < 0.05) means that group counseling with the REBT approach is effective for overcoming anxiety after the flood disaster. The results of this study should be further developed to be able to overcome anxiety that is not only for flood disasters but other anxieties.